Dreaming in Christianity and Islam : culture, conflict, and creativity - Bulkeley, Kelly, 1962-; Adams, Kate, 1965-; Davis, Patricia M., 1955- (Rutgers University Press, 2009)
Dreaming in Christianity and Islam, is the first book to explore dreaming in these religions through original essays. The editors reach a plateau by focusing on how studying dreams reveals new aspects of social and political reality. International scholars document the impact of dreams on sacred texts, mystical experiences, therapeutic practices, and doctrinal controversies.